Application of collisional analysis to the differential velocity of solar wind ions - Johnson, E.; Maruca, B. A.; McManus, M.; Stevens, M.; Klein, K. G.; Mostafavi, P. (Frontiers in Astronomy and Space Sciences, 2024)
Collisional analysis combines the effects of collisional relaxation and large-scale expansion to quantify how solar wind parameters evolve as the plasma expands through the heliosphere.Though previous studies have applied collisional analysis to the temperature ratio between protons (ionized hydrogen) and α-particles (fully ionized helium), this is the first study to explore α-proton differential flow with collisional analysis. First, the mathematical model for the collisional analysis of differential flow was derived. Then, this model was applied to individual in-situ observations from Parker Solar Probe (PSP; r = 0.1−0.27 au) to generate predictions of the α-proton differential flow in the near-Earth solar wind. A comparison of these predicted values with contemporaneous measurements from the Wind spacecraft (r = 1.0 au) shows strong agreement, which may imply that the effects of expansion and Coulomb collisions have a large role in governing the evolution of differential flow through the inner heliosphere.